Factors Influencing The Public Perception Towards Waste Sorting In Manado City - Karouw, Barthe; Santoso, Imam; Koderi (Jurnal Pembangunan dan Alam Lestari, 2024)
Waste sorting is the key to reducing waste. The public's perception affects the level of participation in sorting waste from home, and internal and external factors influence this. This study was conducted to determine the factors that influence the public's perception of waste sorting in Manado City through a descriptive quantitative approach with a survey in the form of a questionnaire. From 928 valid questionnaires analyzed by logistic regression using IBM SPSS Statistics Software, internal factors such as knowledge, expectations, and motivation influence public perceptions towards waste sorting. At the same time, the community effects become an external factor that matters. The economic benefits, necessities, and the government's participation in supporting the community in sorting waste turned out to have no effect. This should concern the Manado City Government so that waste sorting can be more effective and efficient in the future. Keywords: Factors, Perception, Waste, Sorting, Manado